Numerical Simulation of Flood Evolution in Pangtoupao Flood Storage Area Based on Two-Dimensional Shallow Water Equation - SUN Zhenyu; ZHOU Yunhao; ZHANG Qinxu; QIN Mengen; ZHANG Mingliang (Renmin Zhujiang)
Exploring the flood evolution in flood storage areas is of great significance for flood control work in flood storage areas. To predict the dynamics of incoming floods within a short period of time, The Godunov-type finite volume method was used to establish a two-dimensional hydrodynamic numerical model of shallow water. The model had the advantages of adopting unstructured triangular mesh, which could better fit irregular boundaries, and it adopted GPU heterogeneous parallel technology, which effectively solved the problem of slow computation speed of an unstructured network. The model used a limiter to reduce the diffusion and oscillation of second-order precision values. The accuracy of the model simulation was improved effectively by using negative water depth and dry and wet boundary processing techniques. The model was calibrated using multiple dam-break flow experiments and validated with an excellent capability in calculating dry and wet boundaries and static water balance. Flood data from 1998 in the Nenjiang River Basin was used to simulate and calculate flood evolution in the Pangtoupo flood storage area of the Nenjiang River Basin. The results show that the model simulates a storage capacity of 34.9 billion m3 for the Pangtoupo flood storage area, with a relative error of 1.7% compared to the measured value, and a flooded area of 1 267.27 km2, with a relative error of 9.24% compared to the measured value. When different land types in the study area are classified based on roughness coefficients, the simulated storage capacity results of the model approach to the measured values. The parallelized program improves the model's calculation speed by 33%. The model thus can rapidly and accurately calculate the flood evolution process of dam-break flows in complex terrain. The results provide relevant information for flood control planning and disaster warning in flood storage areas.